Penyelesaian Perkara Pidana dengan Menggunakan Prinsip Restorative Justice dalam Perspektif Teori Hukum Progresif oleh Kepolisian dan Kejaksaan - Muhammad Wawan Darmawan; Karim Karim (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The phenomenon of law enforcement in Indonesia today often causes controversy, polemics, resistance, protests or sharp criticism from various groups. The opinions of various parties who disagree with this legal process are often based on the assumption of harming the legal justice of the community who actually no longer agree with the formal legal process through the criminal justice system. One concept that is considered appropriate to overcome various legal problems as described above is to use the restorative justice principle approach. The purpose of this study is to determine the regulation of criminal law related to the settlement of criminal cases by the police and prosecutors by applying the principle of restorative justice based on progressive legal theory. The method used in this study is the normative juridical method. The results of this study provide an overview that: First, Legal regulations related to the settlement of criminal cases by police investigators and prosecutors using the principle of restorative justice are regulated in Articles 13 to 15 of the Chief of Police Regulation Number 8 of 2021 concerning Handling of Criminal Acts Based on Restorative Justice (PTPBKR) and Articles 4, 5 and 6 of the Republic of Indonesia Prosecutor's Office Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice (PPBKR). Second, The procedures for resolving criminal cases using the restorative justice principle approach by the police are regulated in Articles 11 to 18 of the PTPBKR, while the procedures for resolving criminal cases using the restorative justice approach by the prosecutor's office are regulated in Articles 7 to 14 of the PPBKR